Multisystem inflammatory syndrome post-COVID as acute abdominal pain in pediatrics (Revista Argentina de Cirugía, 2026)
We report the case of a 15-year-old adolescent male patient who was admitted to the emergency department due to abdominal pain and fever that started one week before, with negative RT-PCR. The suspected diagnosis was acute appendicitis that was ruled out with complementary tests. The final diagnosis was multisystem inflammatory syndrome associated with COVID-19.
Keywords: COVID 19; multisystem inflammatory syndrome; acute abdomen